Antistatic polycarbonate composition with good cleanliness and preparation method thereof

By using crown ether in antistatic polycarbonate materials to capture metal ions and combining the synergistic effect of compatibility agents and antistatic agents, the problem of metal ions exceeding the standard in the material is solved, achieving both high cleanliness and good antistatic properties.

CN119875344APending Publication Date: 2025-04-25SHANGHAI KUMHOSUNNY JINSHAN PLASTICS CO LTD +1

Patent Information

Application Number
CN202411938063.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing antistatic polycarbonate materials are prone to metal ions exceeding the standard during use, resulting in defects in electronic components, and it is difficult to ensure antistatic performance and cleanliness at the same time.

Method used

Crown ether is used as an ion capture agent to capture metal ions through its ring structure, combining the synergistic effects of compatible agents and antistatic agents to improve the compatibility and antistatic properties of materials and reduce the precipitation of metal ions.

Benefits of technology

It effectively reduces the precipitation of metal ions, improves the cleanliness of the material, and maintains good antistatic properties, avoiding the problem of the reduction of antistatic properties due to ions reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211963800000021
    Figure BDA0005211963800000021
  • Figure BDA0005211963800000061
    Figure BDA0005211963800000061
  • Figure BDA0005211963800000062
    Figure BDA0005211963800000062
Patent Text Reader

Abstract

The invention relates to an antistatic polycarbonate composition with good cleanliness and a preparation method thereof. The antistatic polycarbonate composition comprises polycarbonate, an antistatic agent, an ion capturing agent, a compatilizer, a flexibilizer, an antioxidant, a lubricant and a light stabilizer. According to the invention, crown ether is introduced into antistatic polycarbonate. Under the action of dipole-charge, oxygen atoms with negative electricity of crown ether can be complexed with metal cations with positive electricity to form a relatively stable complex. The ion precipitation performance of a final product is improved by utilizing the capturing capability of a unique annular structure of macromolecular crown ether on metal ions, and the antistatic polycarbonate composition with good cleanliness is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polycarbonate materials, and in particular relates to an antistatic polycarbonate composition with good cleanliness and a preparation method thereof. Background Art

[0002] Conductive or antistatic plastics are widely used in the industrial field due to their advantages such as low cost, easy molding, corrosion resistance, low specific gravity, and electrical conductivity. In some electronic components and semiconductor fields, not only do the parts need to be conductive or antistatic, but they also need to meet high cleanliness requirements. Today's breakthroughs in semiconductor technology have enabled electronic components to have extremely high integration, and this high integration leads to defects and failure of components as long as a very small amount of pollutants (such as particles, metal ions, organic matter, etc.) are introduced during the process, which further reduces the process yield and causes great losses to manufacturers. Therefore, in the semiconductor industry, wafer boat boxes or wafer boxes are generally used as containers for storing wafers so that each wafer can be maintained in a clean state for storage and transportation operations. Many of these wafer boxes are made of antistatic plastic. At this time, the wafer box is in direct contact with the key protected wafer. The cleanliness of the wafer box itself is very critical and is closely related to the yield of the protected wafer.

[0003] As one of the five major engineering plastics, polycarbonate (PC) has advantages such as good optical transparency, impact resistance, thermal stability and electrical insulation. It is widely used in industrial fields such as electronics, automobiles, etc. In the processing and transportation of semiconductor products, antistatic polycarbonate is often used as a transport box, such as a wafer box, a wafer box, a wafer box, an antistatic tray, etc. However, some metal elements often accumulate during the synthesis, production, transportation and storage of polymers or modified plastics, resulting in excessive metal ions in the final plastic parts such as wafer boxes and wafer boxes, resulting in ion precipitation during the subsequent contact with the wafer, causing defects in terminal electronic components. Therefore, it is very important to ensure the cleanliness of antistatic polycarbonate.

[0004] CN117844158A discloses a method for preparing an antistatic composite material, which solves the dispersion problem of carbon nanotubes in a substrate, reduces the agglomeration of carbon nanotubes, and thus reduces the number of surface particles, thereby obtaining an antistatic composite material with good antistatic performance and high surface cleanliness.

[0005] WO2024066693A1 discloses an antistatic polyetheretherketone composite material and a preparation method thereof. The main means is to acidify carbon nanotubes, and at the same time combine a molding process of first making a masterbatch and then mixing and melt extruding and ultrasonic treatment to jointly improve the dispersion of carbon nanotubes in the polyetheretherketone substrate from multiple aspects, thereby ultimately improving the conductivity of the material, reducing dust such as carbon particles on the surface of the material, and obtaining a higher surface cleanliness.

[0006] TW201701391A discloses a cycloolefin composition, in which 1% to 5% by weight of carbon nanotubes are added to the cycloolefin, and a semiconductor substrate transfer box based on the cycloolefin composition. The product shows a lower concentration of harmful ions than liquid crystal polymers and carbon fiber composites. However, the inventor did not point out the reason, and cycloolefins are expensive and have many performance limitations, such as poor toughness.

[0007] In general, current research on improving the cleanliness of antistatic materials mainly focuses on how to reduce dust precipitation, reduce decarbonization, or how to reduce the migration of the antistatic agent itself. There is relatively little research on how to reduce the precipitation of metal ions. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide an antistatic polycarbonate composition with good cleanliness and a preparation method thereof.

[0009] The purpose of the present invention can be achieved through the following technical solutions.

[0010] In a first aspect, the present invention discloses an antistatic polycarbonate composition with good cleanliness, comprising the following raw material components in percentage by weight:

[0011]

[0012] As an embodiment of the present invention, the polycarbonate includes one or more of aromatic polycarbonate and aliphatic polycarbonate. Preferably, it is any one or a combination of at least two thereof, more preferably aromatic polycarbonate, and more preferably bisphenol A polycarbonate. The amount of polycarbonate used is preferably 74% to 86%.

[0013] Preferably, the melt index of the polycarbonate is 1 to 50 g / 10 min at 300° C. and 1.2 kg; more preferably, the melt index is 2 to 25 g / 10 min.

[0014] As an embodiment of the present invention, the antistatic agent is a copolymer macromolecular antistatic agent, and the copolymer macromolecular antistatic agent includes one or more of polyether polyamide block copolymer and polyether polyester copolymer.

[0015] Preferably, the surface resistivity of the copolymer macromolecular antistatic agent is preferably 1E5 to 1E10 Ω / sq, and more preferably 1E5 to 1E8 Ω / sq.

[0016] Preferably, the mass percentage of the antistatic agent is 12-18%.

[0017] As an embodiment of the present invention, the ion capture agent is a crown ether compound. The weight percentage of the ion capture agent is preferably 0.3%-1%, more preferably 0.3%-0.7%.

[0018] The crown ether compound of the present invention can be selected from various substances generally known as crown ethers according to the purpose. As a crown ether, the one with the simplest structure is a crown ether having the general formula (-CH2-CH2-O-): n In the present invention, the substance in which n is 4 to 7 is preferred. In the case of a crown ether, the total number of atoms constituting the ring is x and the number of oxygen atoms contained therein is y, and it is sometimes referred to as x-crown-y-ether.

[0019] Preferably, the crown ether compound includes 12-crown-4, 15-crown-5, 18-crown-6, 21-crown-7 and derivatives thereof. In the present invention, it is preferred to use at least one selected from the group consisting of crown ethers with x=12, 15, 18 or 21, y=x / 3, their benzo condensates and cyclohexyl condensates. Specific examples of more preferred crown ethers include 21-crown-7-ether, 18-crown-6-ether, 15-crown-5-ether, 12-crown-4-ether, dibenzo-21-crown-7-ether, dibenzo-18-crown-6-ether, dibenzo-15-crown-5-ether, dibenzo-12-crown-4-ether, dicyclohexyl-21-crown-7-ether, dicyclohexyl-18-crown-6-ether, dicyclohexyl-15-crown-5-ether, dicyclohexyl-12-crown-4-ether and the like. Among them, it is most preferable to select from 12-crown-4, 15-crown-5, 18-crown-6 and 21-crown-7. It may be a combination of one or more of the following: benzo-18-crown-6, benzo-15-crown-5, diaza-18-crown-6.

[0020] For the antistatic property of polycarbonate, antistatic agent is added, but the addition of antistatic agent can bring metal cation, and its precipitation can make the metal ion of product exceed the standard, and metal ion precipitation or reduction can increase surface resistance, and antistatic property can be decreased, and the two are difficult to coordinate. The ring structure of crown ether compound used in the present invention can improve the ion precipitation property of final product to the metal ion capture ability, but because metal ion is reduced (captured), it usually causes surface resistance to increase, antistatic property can be decreased, and it can not be used at the same time in theory. But the inventor found in actual experiment that under the suitable crown ether dosage, although the number of cations is reduced, the antistatic property of material, i.e., surface resistance, is not greatly affected. Further research finds that because crown ether can further promote the compatibility of system, it is conducive to the construction of charge dissipation channel of polyether segment (antistatic agent), that is, crown ether has certain volume expansion effect, when adding in small amount, volume expansion effect is greater than capture effect (but the captured ions are few) or substantially equivalent, and electrical path material can even show slight improvement of antistatic property, which depends on the capture ability of crown ether and the influence of dosage. The crown ether used in the present invention, when in an amount of about 0.5%, can have both the effects of capturing and increasing the volume, thereby ensuring the antistatic property of the polycarbonate and significantly reducing the precipitation of metal ions.

[0021] As an embodiment of the present invention, the compatibilizer includes one or more of styrene-acrylonitrile grafted maleic anhydride resin, acrylonitrile-butadiene-styrene grafted maleic anhydride resin, styrene-acrylonitrile grafted glycidyl methacrylate resin, acrylonitrile-butylene-styrene grafted glycidyl methacrylate resin and polystyrene grafted maleic anhydride resin. The weight percentage of the compatibilizer is preferably 0.4%-1.5%.

[0022] As an embodiment of the present invention, the toughening agent includes any one or more of methyl methacrylate-butadiene-styrene graft copolymer and core-shell toughening agent. Among them, the core of the core-shell toughening agent is silicone / acrylate, and the shell is methyl methacrylate. Specifically, the core-shell toughening agent includes but is not limited to one or more of Mitsubishi's S-2001, S-2501, S-2030, S-2100, SX-005, and Japan's MR-01. Methyl methacrylate-butadiene-styrene graft copolymer includes but is not limited to one or more of Japan's M732KM and M-521.

[0023] As an embodiment of the present invention, the antioxidant includes one or more of phosphite antioxidants, hindered phenol antioxidants, and thioester antioxidants. More preferably, the antioxidant is one or a mixture of antioxidant 168, antioxidant 1010, antioxidant 1076, antioxidant 1098, and antioxidant 300.

[0024] As an embodiment of the present invention, the lubricant is one or both of pentaerythritol stearate and ethylene bisstearamide.

[0025] As an embodiment of the present invention, the light stabilizer is one or more of benzophenone light stabilizers, benzotriazole light stabilizers, salicylate light stabilizers, substituted acrylonitrile light stabilizers and triazine light stabilizers. More preferably, the light stabilizer is one or more of Tinuvin-P Uvinul 3033P, Tinuvin-327, Tinuvin-329, Tinuvin-234 and 328.

[0026] In a second aspect, the present invention discloses a method for preparing an antistatic polycarbonate composition having good cleanliness as described above, comprising the following steps:

[0027] S1: mixing the raw material components in a mixer to obtain a premix;

[0028] S2: The mixture obtained in step S1 is placed in a twin-screw extruder, and after melt extrusion and granulation, an antistatic polycarbonate composition with good cleanliness is obtained.

[0029] Among them, the screw speed is 400-800rpm, the twin-screw extruder includes ten temperature control zones, the temperature of temperature control zone 1-2 is 200-280℃, the temperature of temperature control zone 3-4 is 200-280℃, the temperature of temperature control zone 5-6 is 200-280℃, the temperature of temperature control zone 7-8 is 200-280℃, and the temperature of temperature control zone 9-10 is 200-280℃.

[0030] The twin-screw extruder has two vacuuming locations, one located at the end of the conveying section and the beginning of the melting section; and the other located at the metering section.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The present invention introduces crown ethers into antistatic polycarbonate. Under the action of dipole-charge, the negatively charged oxygen atoms of the crown ethers can form relatively stable complexes with positively charged metal cations. By utilizing the unique ring structure of the crown ethers to capture metal ions, the ion precipitation performance of the final product is improved.

[0033] (2) The present invention has found that in the polycarbonate / macromolecular antistatic agent system of the present invention, the synergistic effect of the compatibilizer and the crown ether can improve the shortcoming that the finished product is easy to peel. It is speculated that the reason may be that the low molecular weight crown ether, with its ether bond structure, has a certain compatibility with polycarbonate containing a large number of carbonate bonds and antistatic agents containing a large number of ether bonds, thereby reducing the compatibility difference between the substrate phase and the antistatic agent phase. After the synergistic effect with the compatibilizer, the phase interface effect is strengthened, so that the injection molded product gate and the like are less likely to peel. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0035] In the following description, unless otherwise specified, the reagents used are conventional commercial products, and the methods used are conventional means in the art.

[0036] The following describes the various raw material components used in this embodiment:

[0037] PC: bisphenol A polycarbonate, commercially available, PC2100 product purchased from Wanhua, MI=10 g / 10 min (300° C., 1.2 kg).

[0038] Antistatic agent: It is a polyamide macromolecular antistatic agent, a permanent antistatic agent TR-400 purchased from Hangzhou Lingyou Technology Co., Ltd., with a surface resistance of 5E6.

[0039] Ion trapping agents: crown ethers, benzo-18-crown-6, benzo-15-crown-5, purchased from Sigma Aldrich;

[0040] Toughening agent: methyl methacrylate-butadiene-styrene graft copolymer, M-521, Nakabune, Japan;

[0041] Compatibilizer: styrene-acrylonitrile-glycidyl methacrylate terpolymer, SAG-005, Jiayirong.

[0042] Lubricant: Pentaerythritol stearate, commercially available.

[0043] Antioxidant: Irganox 168 and Irganox 1010 mixed in a mass ratio of 1:1, commercially available.

[0044] Light stabilizer: benzotriazole UV absorber, commercially available.

[0045] Examples 1-6

[0046] This embodiment provides an antistatic polycarbonate composition with good cleanliness and a preparation method thereof, wherein the preparation steps are as follows:

[0047] S1: According to the formula in Table 1, polycarbonate, antistatic agent, ion scavenger, compatibilizer, toughening agent, antioxidant, lubricant, and light stabilizer are mixed in a mixer to obtain a premix;

[0048] S2: The mixture obtained in step S1 is placed in a twin-screw extruder (two vacuum locations, one located at the end of the conveying section and the beginning of the melting section; the other located at the metering section), the screw speed is 600 rpm, and the temperatures of each screw zone are 210°C, 230°C, 240°C, 250°C, 250°C, 240°C, 230°C, 235°C, 240°C, and 250°C. After extrusion and granulation, an antistatic polycarbonate composition with good cleanliness is obtained.

[0049] Table 1 Resin composition formula (percentage content)

[0050]

[0051] Comparative Examples 1-10

[0052] This comparative example provides an antistatic polycarbonate composition with good cleanliness and a preparation method thereof. The preparation steps are basically the same as those in Example 1, and the mass fractions of the components are shown in Table 2.

[0053] Table 2 Resin composition formula of comparative example (percent content)

[0054]

[0055] Performance test, the test method is as follows:

[0056] The bending performance is tested according to ISO178 standard, with a bending rate of 2mm / min.

[0057] The heat deformation temperature is tested according to ISO75-1 standard, with a load weight of 1.80 MPa and a heating rate of 120°C / min.

[0058] The notched impact test of the simply supported beam was carried out according to ISO 179-1 standard and was conducted on a Zwick electronic universal testing machine.

[0059] Surface resistance: Tested in accordance with ASTM D257-2014; injection molded 70*130*3mm square plate specimens, using ZST-12 insulating material volume surface resistance (rate) tester.

[0060] Cleanliness test: The material is injection molded into a sheet of 63.5*12.7*3.2mm, and 5 sheets are placed in 2L ultrapure water, ultrasonicated for 15 minutes, and the remaining liquid after the product is taken out is used as the test liquid. Then an ion chromatograph is used to test the amount of metal cation precipitation. The total amount of ions includes: lithium ions (Li + ), sodium ion (Na + ), potassium ion (K + ), calcium ions (Ca 2+ ), magnesium ion (Mg 2+ ), aluminum ions (Al 3+ ), titanium ions (Ti 2+ ), chromium ion (Cr), manganese ion, zinc ion, copper ion, nickel ion, manganese ion and other common ions, the unit is converted into (ppb, μg / kg).

[0061] Characterization of anti-peeling performance: Fold the bent spline repeatedly, and use the number of bends when obvious delamination and peeling begin to indicate the anti-peeling performance. The larger the value, the less likely it is to peel.

[0062] The test results are shown in Table 3.

[0063] Table 3 Properties of the resin compositions of the examples and comparative examples

[0064]

[0065]

[0066] By comparing Example 2 and Comparative Example 2, and Example 6 and Comparative Example 8, it can be found that after the introduction of the ion capture agent crown ether, the number of metal cations detected by the material will be objectively reduced, and the cleanliness will be improved. However, it is magically found that although the number of cations has decreased, the antistatic performance of the material, that is, the surface resistance, is not greatly affected. It is speculated that the reason is that the electrostatic dissipative molecular network mainly relies on the electrical path constructed by the charge dissipation channel of the polyether segment (antistatic agent), and the reduction of harmful metal cations only accounts for a part of the overall cation level, and the number of anions in the system is not significantly affected, so the electrical properties do not show obvious fluctuations when a small amount of crown ether is added, and even because the crown ether can further promote the compatibility of the system, the material also shows a slight improvement in antistatic performance.

[0067] The effect of crown ether in capturing metal ions will increase resistance, but crown ether itself has a certain compatibility with polymer substrate and antistatic phase, so there is a slight effect of promoting compatibility, which will also help reduce resistance. When the percentage of crown ether is below 0.5%, cations are basically captured, and the capacity-increasing effect is relatively obvious, so the antistatic performance does not decrease due to the reduction of ions, but the antistatic effect may be better after the crown ether is added.

[0068] From the comparison between Example 2 and Comparative Examples 2-3, and Example 6 and Comparative Examples 8-9, it can be found that after the crown ether and the compatibilizer are compounded, the anti-skinning performance of the material is better than that of the two alone. It is speculated that the crown ether and the compatibilizer synergistically improve the compatibility of the system.

[0069] From the comparison between Example 1 and Comparative Example 6, it can be seen that when too little crown ether is added, the ion content of the material is still relatively high. From the comparison between Examples 1, 2, 5 and Comparative Example 4, it can be seen that as the crown ether content increases, the number of metal cations in the material will decrease, but when its content is higher than 1%, the increase in the number of crown ethers at this time will reduce the number of metal cations to a very limited extent, but the material will not only significantly reduce heat resistance, but also reduce antistatic performance. It is speculated that this may be due to the small molecular weight of the crown ether. When too much crown ether is added, an enrichment layer is formed on the surface, thereby affecting the surface resistance of the material.

[0070] From the comparison between Example 2 and Comparative Example 5, it can be found that the compatibilizer should not be added too much, because the conductivity mainly depends on the conductive network formed by the antistatic agent in the polycarbonate substrate. When the compatibility is too good, it is easy to promote the continuous phase separation structure to transform into a dispersed sea island structure, thereby destroying the conductive network and reducing the antistatic performance.

[0071] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. An antistatic polycarbonate composition, characterized in that: The raw material components include the following weight percentages:

2. The antistatic polycarbonate composition according to claim 1, characterized in that The polycarbonate includes one or more of aromatic polycarbonate and aliphatic polycarbonate.

3. The antistatic polycarbonate composition according to claim 1, characterized in that The antistatic agent is a copolymer macromolecular antistatic agent, including one or more of polyether polyamide block copolymers and polyether polyester copolymers.

4. The antistatic polycarbonate composition according to claim 1, characterized in that: The ion capture agent is a crown ether compound, including one or more of 12-crown-4, 15-crown-5, 18-crown-6, 21-crown-7, or one or more of their derivatives.

5. The antistatic polycarbonate composition according to claim 1, characterized in that: The compatibilizer includes one or more of styrene-acrylonitrile grafted maleic anhydride resin, acrylonitrile-butadiene-styrene grafted maleic anhydride resin, styrene-acrylonitrile grafted glycidyl methacrylate resin, acrylonitrile-butylene-styrene grafted glycidyl methacrylate resin and polystyrene grafted maleic anhydride resin.

6. The antistatic polycarbonate composition according to claim 1, characterized in that: The toughening agent includes any one or more of methyl methacrylate-butadiene-styrene graft copolymer and core-shell structure toughening agent.

7. The antistatic polycarbonate composition according to claim 1, characterized in that: The antioxidant includes one or more of phosphite antioxidants, hindered phenol antioxidants, and thioester antioxidants.

8. The antistatic polycarbonate composition according to claim 1, characterized in that: The lubricant is one or two of pentaerythritol stearate and ethylene bisstearamide.

9. The antistatic polycarbonate composition according to claim 1, characterized in that: The light stabilizer is one or more of benzophenone light stabilizers, benzotriazole light stabilizers, salicylate light stabilizers, substituted acrylonitrile light stabilizers, and triazine light stabilizers.

10. A method for preparing the antistatic polycarbonate composition according to claim 1, characterized in that: The steps include: S1: mixing the raw material components uniformly to obtain a premix; S2: The premix obtained in step S1 is melt-extruded and granulated to obtain an antistatic polycarbonate composition.

Citation Information

Patent Citations

  • Preparation method and application of antistatic composite material

    CN117844158A

  • A cycloolefin composition and a cycloolefin semiconductor substrate transport box made of the same

    TW201701391A

  • Antistatic polyether-ether-ketone composite material and preparation method therefor

    WO2024066693A1

Cited By

  • Antistatic polycarbonate composition having good cleanliness and preparation method therefor

    WO2026137844A1